Deprescribing NSAIDs: The Potential Role of Community Pharmacists - Delsher Amedi; Parisa Gazerani (MDPI AG, 2024)
Non-steroidal anti-inflammatory drugs (NSAIDs) are largely used for controlling various pain conditions and are widely available in community pharmacies, with and without prescription. Despite their effectiveness, NSAIDs can pose significant risks due to potential side effects and drug interactions, particularly in polypharmacy and comorbidity contexts and for vulnerable users. This study investigated whether and how NSAIDs deprescribing can be conducted at the community pharmacy level by assessing pharmacists' confidence, attitudes, and potential barriers and facilitators. Additionally, we aimed to identify any deprescribing guidelines that pharmacists could use. A literature search and a cross-sectional digital questionnaire targeting community pharmacists in Norway were conducted. Results showed that study participants (N = 73) feel confident in identifying needs for deprescribing NSAIDs but barriers such as time constraints, lack of financial compensation, and communication challenges were noted. Participants reported positive attitudes toward deprescribing but highlighted a need for better guidelines and training. This study highlights a gap in specific guidelines for deprescribing NSAIDs and a potential for enhancing pharmacists' roles in the deprescribing process, for example, through training and improved financial incentives. Further research is encouraged to develop concrete strategies for an effective implementation where community pharmacists can be involved in the deprescribing of NSAIDs.